PENGARUH HARGA MINYAK DUNIA DAN SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 1987-2017 - Ina Yanti; Ratna Ratna (Jurnal Ekonomi Regional Unimal, 2019)
This study aims to determine the effect of world oil prices and interest rates on the economic growth of Indonesia. The data used in this study is time-series data during1987-2017 obtained from Indonesia. (Energy Information Administration), Bank Indonesia, and the Central Bureau of Statistics. Data analysis methods use multiple linear regression and Vector Autoregression (VAR) models. The results of the study show that partially the world oil prices and interest rates have a significant and negative effect on the economic growth of Indonesia. Simultaneously, world oil prices and interest rates have a significant and positive effect on the economic growth of Indonesia. Furthermore, the results of testing the VAR analysis model indicate that world oil prices have a positive and significant effect on the economic growth of Indonesia, and interest rates have a positive and insignificant effect on the economic growth of Indonesia. It recommends that the government and all stakeholders must collaborate to reduce or eliminate the influence of shocks to global oil prices domestically and a concrete step that needs to be sought is to normalize the habits that used to be wasteful of fuel to save fuel.